Compare the effect of vaginal cream hydroalcoholic extracts of oregano (Mentha longifolia L.), mint (Mentha piperata L.) and savory (Satureja hortensis L.) with metronidazole vaginal gel in the treatment of Bacterial vaginosis - Eghbal, Hojjat; Moazzenzadeh, Omid; Mohammadi, Elshan; Feyzi, Samaneh (International Pharmacy Acta, 2018)
Abstract: Bacterial vaginosis is caused by an overgrowth of anaerobic bacteria. And a common complication of the vagina in women of childbearing age and cause premature rupture of membranes labor pain, premature birth and infant and often accompanied by secretions thin, smooth, gray and with a bad smell fish, that vaginal mucosa to form of uniform layer cover , the finds manifestation. Side effects and drug resistance of chemical drugs, cause research on herbal drugs continue without complications. According to the therapeutic effects of plants such as oregano, mint and fennel on bacterial organisms We hope this study can be identified by the use of herbal drug combination. Methods and Results: This study is a randomized clinical trial on 80 married women 18-44 years old with Bacterial vaginosis with itching, complaining of vaginal discharge, burning sensation, dyspareunia and dysuria during the 6-month visit to the health center No. 5 meshkinshar had been completed. These individuals were divided randomly into two groups of 40 patients treated with vaginal cream mixed tertiary extract and, metronidazole vaginal gel 0.75 percent. The research was conducted in various stages of clinical practice. Complaints of patients before and after treatment in both treatment groups showed a significant difference. but between the two treatment groups in terms of vaginal cream teas and metronidazole gel complaints did not see a significant difference after treatment. amsel criteria before treatment and after treatment in both groups treated with medications, there was a significant difference. Amsel criteria after treatment between the two groups in herbal vaginal cream and metronidazole vaginal gel, a significant difference was observed. Conclusions: Findings indicate that herbal vaginal cream 5%, and metronidazole vaginal gel in reducing complaints have been similar to patients with bacterial vaginosis. And, to improve Amsel criteria have the same effect. So vaginal cream 5% of tertiary mixture of extracts can be considered a viable alternative for metronidazole vaginal gel in the treatment of bacterial vaginosis.